Championing nutrition: Effective leadership for action [Nourishing Millions] - Nisbett, Nicholas; Wach, Elise; Haddad, Lawrence James; El Arifeen, Shams; Reddin, Samantha; Gatellier, Karine; Covic, Namukolo; Drimie, Scott; Harris, Jody; Yosef, Sivan (2016)
THE CALLS FOR strong leadership in the fight against global and national malnutrition have multiplied during the past decade. The role of nutrition champions in advocating for nutrition, formulating policies, and coordinating and implementing action in nutrition have increasingly been recognized in such countries as Peru, Brazil, Thailand, and the Indian states of Tamil Nadu and Maharashtra. Global initiatives such as the Scaling Up Nutrition (SUN) Movement, the African Nutrition Leadership Programme, and the European Nutrition Leadership Platform have invested in building up capacity for leadership among national governments, civil society, and the private sector. The World Public Health Nutrition Association’s guide on competencies needed to build up the workforce in global public health nutrition identified leadership as key. More widely, leadership within the field of public health has been highlighted as key to moving child or maternal health higher up on the global agenda and tackling critical issues such as HIV and AIDS at the national and community levels.